PEMANFAATAN DIGITAL LIBRARY LET’S READ SEBAGAI MATERI BAHAN AJAR BAHASA INGGRIS UNTUK READING AND SPEAKING - Siti Maria Ulfa; Hendra Sudarso (Jurnal Abdi Masyarakat, 2020)
AbstractThe breakthrough in Information Communication Technology (ICT) has brought new opportunities to restructure language learning. At present, ICT has opened new avenues and brought new challenges for language learners and also teachers. The responsibility of the learning task has shifted towards students and this has dramatically changed the role of the teacher. However, it should be noted that modern language teachers determine the quality of the learning process, not ICT itself. This paper tries to highlight the potential of ICT as a powerful tool for teaching foreign languages and the effect of this technology on second language learning. The community service program emphasizes the use of the Lets Read link as a forum to find teaching materials for Excellent Course teachers. Along with the development of technology as it is today, teachers must also be more flexible in finding teaching materials for their students, especially in learning English. Therefore, it is necessary for teachers to know useful links that can be used in learning in their class.Keywords: Language Learning, ICT, Let’s Read Application  AbstrakTerobosan Teknologi Komunikasi Informasi (TIK) telah membawa peluang baru untuk merestrukturisasi pengaturan pembelajaran / pengajaran bahasa. Saat ini, TIK telah membuka jalan baru dan membawa tantangan baru bagi pembelajar bahasa dan juga guru. Tanggung jawab tugas belajar telah bergeser ke arah peserta didik dan ini telah secara dramatis mengubah peran guru. Namun, perlu dicatat bahwa guru bahasa modern menentukan kualitas proses pembelajaran, dan bukan TIK. Makalah ini mencoba untuk menyoroti potensi TIK sebagai alat yang kuat untuk pengajaran bahasa asing dan efek dari teknologi ini pada pembelajaran bahasa kedua. Program pengabdian masyarakat menekankan pada pemanfaatan link Lets Read sebagai wadah pencarian bahan ajar bagi guru-guru LKP Excellent Course. Seiring dengan berkembangnya teknologi seperti sekarang ini, guru juga harus lebih luwes dalam mencari bahan ajar untuk siswanya kususnya dalam pembelajaran Bahas Inggris. Maka dari itu, perlu bagi guru-guru mengetahui link yang bermanfaat yang dapat digunakan dalam pembelajaran dikelas mereka.Kata kunci: Pembelajaran Bahasa, Telnologi Komunikasi dan Informasi,l Aplikasi Let’s Read